Myeloperoxidase-derived oxidants induce blood-brain barrier dysfunction in vitro and in vivo. - Andreas Üllen; Evelin Singewald; Viktoria Konya; Günter Fauler; Helga Reicher; Christoph Nusshold; Astrid Hammer; Dagmar Kratky; Akos Heinemann; Peter Holzer; Ernst Malle; Wolfgang Sattler (PLoS ONE)
Peripheral leukocytes can exacerbate brain damage by release of cytotoxic mediators that disrupt blood-brain barrier (BBB) function. One of the oxidants released by activated leukocytes is hypochlorous acid (HOCl) formed via the myeloperoxidase (MPO)-H2O2-Cl(-) system. In the present study we examined the role of leukocyte activation, leukocyte-derived MPO and MPO-generated oxidants on BBB function in vitro and in vivo. In a mouse model of lipopolysaccharide (LPS)-induced systemic inflammation, neutrophils that had become adherent released MPO into the cerebrovasculature. In vivo, LPS-induced BBB dysfunction was significantly lower in MPO-deficient mice as compared to wild-type littermates. Both, fMLP-activated leukocytes and the MPO-H2O2-Cl(-) system inflicted barrier dysfunction of primary brain microvascular endothelial cells (BMVEC) that was partially rescued with the MPO inhibitor 4-aminobenzoic acid hydrazide. BMVEC treatment with the MPO-H2O2-Cl(-) system or activated neutrophils resulted in the formation of plasmalogen-derived chlorinated fatty aldehydes. 2-chlorohexadecanal (2-ClHDA) severely compromised BMVEC barrier function and induced morphological alterations in tight and adherens junctions. In situ perfusion of rat brain with 2-ClHDA increased BBB permeability in vivo. 2-ClHDA potently activated the MAPK cascade at physiological concentrations. An ERK1/2 and JNK antagonist (PD098059 and SP600125, respectively) protected against 2-ClHDA-induced barrier dysfunction in vitro. The current data provide evidence that interference with the MPO pathway could protect against BBB dysfunction under (neuro)inflammatory conditions.